ANALISIS KEBUTUHAN PENGEMBANGAN LKPD BERBASIS AKM TERINTEGRASI NILAI RELIGIUS UNTUK MENINGKATKAN PEMBELAJARAN HIDROKARBON - Merina, Dana; Ayi Darmana; Nurfajriani (Jurnal Tunas Pendidikan, 2026)
This study aims to analyze the needs of teachers and students for the development of Learner Worksheets (LKPD) based on Minimum Competency Assessment (AKM) integrated with religiosity values in learning chemistry on hydrocarbon material. The background of this research is based on the low learning outcomes of students, the weak integration of character values in learning, and the unoptimal use of LKPDs that support mastery of literacy, numeracy, and the cultivation of moral values. The research method used is a qualitative descriptive approach at the analysis stage of the ADDIE model. Data were obtained through interviews and questionnaires distributed to teachers and students of grade XI high school. The results of the analysis show that the LKPD that has been used so far is still textual, has not developed aspects of critical and reflective thinking according to the demands of AKM, and has not accommodated the strengthening of religious character. Teachers expressed the importance of developing LKPDs that integrate religious values such as honesty, responsibility, and gratitude for God's creation in science materials. Meanwhile, students want teaching materials that are interactive, contextual, and value-inspiring. Therefore, it is necessary to develop an AKM-based LKPD that not only improves understanding of hydrocarbon material, but also strengthens the religious character of students as a whole in accordance with the Pancasila Student Profile.